An integrated analysis of carbon capture and storage strategies for power and industry in Europe. (20th December 2021) - Turgut, Ozgu; Bjerketvedt, Vegard Skonseng; Tomasgard, Asgeir; Roussanaly, Simon
Abstract: Industry is responsible for one-quarter of the global CO2 emissions. In this study, four different climate pathways are analyzed with a cost minimizing multihorizon stochastic optimization model, in order to analyze possible realizations of carbon capture and storage (CCS) in the power sector and main industrial sectors in Europe. In particular, we aim to achieve a deeper understanding of the distribution of capture by country and key sector (power, steel, cement and refinery), as well as the associated transport and storage infrastructure for CCS. Results point to the synergy effect of sharing common CCS infrastructres among power and major industrial sectors. The contribution of CCS is mainly found in three industrial sectors, particularly steel, cement and refineries) but also in the power sector to a lesser extent. It is worth noting that retrofitting of CCS in the power sector was not considered in this study. The geographical location for capture and storage, as well as timing and capacity needs are presented for different socio-economic pathways and corresponding emission targets. It has been shown that contributions of the three industry sectors in emissions reductions are neither geographically nor sector-wise homogeneous across the pathways. Highlights: Study of potential synergies between shared CCS infrastructure in the power sector and industry. Study of the interplay between CCS and renewables in the power sector. CCS strategies for the steel, cement and refinery sectors of Europe. Timing and investment volumes needed to capture, transport and store CO2 . Guided by climate targets of socio-economic pathways of IPCC.